2023
DOI: 10.3390/ma16031234
|View full text |Cite
|
Sign up to set email alerts
|

Degradation Mechanism of Coal Gangue Concrete Suffering from Sulfate Attack in the Mine Environment

Abstract: Recycling coal gangue as aggregate to produce concrete in situ is the most effective way to solve the problem of deposited coal gangue in mines. Nevertheless, the mine environment underground is rich in sulfate ions, posing a threat to the durability of coal gangue concrete (CGC). Hence, the degradation process of sulfate-attacked CGC is investigated. A series of tests is performed to evaluate its variation law of mass, dynamic elastic modulus, compressive strength and sulfate ion distribution. Meanwhile, the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…The alterations in crystal phases of the R0, R1, R4 and R7 samples under ambient conditions and subsequent exposure to high temperatures were determined through X-ray diffraction (XRD) analysis, as illustrated in Figure 12a-d. The primary phases in all samples under ambient conditions were identified as portlandite (CH), calcium-silicate-hydrate (C-S-H), and quartz (Q) [64,65]. However, distinct from the R0 control sample, the FA-doped R1, R4, and R7 samples exhibited crystal phases of calcite (CaCO 3 ) and mullite (Al 6 Si 2 O 13 ) in addition to these primary phases [66,67].…”
Section: Xrd Analysismentioning
confidence: 99%
“…The alterations in crystal phases of the R0, R1, R4 and R7 samples under ambient conditions and subsequent exposure to high temperatures were determined through X-ray diffraction (XRD) analysis, as illustrated in Figure 12a-d. The primary phases in all samples under ambient conditions were identified as portlandite (CH), calcium-silicate-hydrate (C-S-H), and quartz (Q) [64,65]. However, distinct from the R0 control sample, the FA-doped R1, R4, and R7 samples exhibited crystal phases of calcite (CaCO 3 ) and mullite (Al 6 Si 2 O 13 ) in addition to these primary phases [66,67].…”
Section: Xrd Analysismentioning
confidence: 99%
“…Analysing the invert of the tunnel, especially for type 1 soils, the decompressions in the tunnel contour and the infiltration flows suggest the possibility of a liquefaction of the sands. In the case of using segments in the tunnel lining, the joints must be treated with a specific fibre-reinforced concrete [65,66], suitable for the type of soil (particularly in mining tunnels) [67,68], or water-repellent additives [40].…”
Section: Total Stress and Effective Stress In The Domainmentioning
confidence: 99%
“…Analysing the invert of the tunnel, es- flows suggest the possibility of a liquefaction of the sands. In the case of using segments in the tunnel lining, the joints must be treated with a specific fibre-reinforced concrete [65,66], suitable for the type of soil (particularly in mining tunnels) [67,68], or water-repellent additives [40]. It was observed that in the less compact soils (Figure 7a,c), the decompressed zones in the contour and adjacent areas of the crown and invert tunnel were somewhat larger.…”
Section: Total Stress and Effective Stress In The Domainmentioning
confidence: 99%
“…In this process, pore structure distributions in the hydrated binder have also been refined [13], which is reflected in the reduction in the large pores and formation of more gel pores with lower size. More importantly, the pore structure refinement and ion consolidation ability of C-A-S-H gel are also favorable for resisting the penetration and transmission of corrosive ions, such as Cl − and SO 4 2− [14]. Therefore, CCG-blended cement also secure satisfactory long-term durabilities in severe environments as compared with the corresponding reference samples.…”
Section: Introductionmentioning
confidence: 99%